Computational‐driven epitope verification and affinity maturation of tlr4‐targeting antibodies - Ahmad, Bilal; Batool, Maria; Kim, Moon Suk; Choi, Sangdun (International Journal of Molecular Sciences, 2021)
Toll‐like receptor (TLR) signaling plays a critical role in the induction and progression of autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematous, experimental autoimmune encephalitis, type 1 diabetes mellitus and neurodegenerative diseases. Deciphering antigen recognition by antibodies provides insights and defines the mechanism of action into the progression of immune responses. Multiple strategies, including phage display and hybridoma tech-nologies, have been used to enhance the affinity of antibodies for their respective epitopes. Here, we investigate the TLR4 antibody‐binding epitope by computational‐driven approach. We demon-strate that three important residues, i.e., Y328, N329, and K349 of TLR4 antibody binding epitope identified upon in silico mutagenesis, affect not only the interaction and binding affinity of antibody but also influence the structural integrity of TLR4. Furthermore, we predict a novel epitope at the TLR4‐MD2 interface which can be targeted and explored for therapeutic antibodies and small mol-ecules. This technique provides an in‐depth insight into antibody–antigen interactions at the resolution and will be beneficial for the development of new monoclonal antibodies. Computational techniques, if coupled with experimental methods, will shorten the duration of rational design and development of antibody therapeutics.
Keywords: Amino Acid Sequence; Antibodies, Monoclonal; Arthritis, Rheumatoid; Cell Surface Display Techniques; Encephalitis; Epitope Mapping; Epitopes; Hashimoto Disease; Humans; Neurodegenerative Diseases; Protein Binding; Toll-Like Receptor 4; Antibody; Epitope; Molecular dynamics; Mutation; Toll‐like receptor